Rugby-playing history at the national U13 level and subsequent participation at the national U16 and U18 rugby tournaments - Durandt, Justin; Parker, Ziyaad; Masimla, Herman; Lambert, Mike (South African Journal of Sports Medicine, 2011)
Background. The South African Rugby Union has adopted the model of competition at a young age (U13 years) to identify talent. There is concern however that bigger players who mature early are selected at this age, and that the majority of these players do not play rugby at a high level after puberty. Objectives. The aim of this study was to establish how many players in the 2005 U13 Craven week (n=349) participated in subsequent U16 Grant Khomo and U18 Craven week tournaments. Design. Longitudinal. Results. 31.5% of the players who played in the U13 Craven week, were again selected to play at U16 Grant Khomo week and 24.1% were selected for the U18 Craven week. Conclusion. Seventy-six per cent of the players selected for the U13 tournament do not play at the U18 national Craven week tournament. These data need to be considered when decisions are made about the cost-effectiveness of staging the U13 tournament, particularly if the main goal of this tournament is for talent identification. SAJSM, vol 23 No. 4 2011